Understanding Inherited Risk in Unselected Newly Diagnosed Patients With Endometrial Cancer. Issue 8 (August 2019) - Cadoo, Karen A.; Mandelker, Diana L.; Mukherjee, Semanti; Stewart, Carolyn; DeLair, Deborah; Ravichandran, Vignesh; Srinivasan, Preethi; Hurley, Daire; Kemel, Yelena; Arnold, Angela G.; Sheehan, Margaret; Pradhan, Nisha; et al.
Abstract : (Abstracted from JCO Precision Oncology 2019; doi: 10.1200/PO.18.00338) Endometrial cancer remains the most common gynecologic malignancy. Fortunately, approximately 70% of patients present with an early-stage disease with curative options.